Association between male circumcision and women's biomedical health outcomes: a systematic review. Issue 11 (November 2017) - Grund, Jonathan M; Bryant, Tyler S; Jackson, Inimfon; Curran, Kelly; Bock, Naomi; Toledo, Carlos; Taliano, Joanna; Zhou, Sheng; del Campo, Jorge Martin; Yang, Ling; Kivumbi, Apollo; Li, Peizi; et al.
Summary: Background: Male circumcision reduces men's risk of acquiring HIV and some sexually transmitted infections from heterosexual exposure, and is essential for HIV prevention in sub-Saharan Africa. Studies have also investigated associations between male circumcision and risk of acquisition of HIV and sexually transmitted infections in women. We aimed to review all evidence on associations between male circumcision and women's health outcomes to benefit women's health programmes. Methods: In this systematic review we searched for peer-reviewed and grey literature publications reporting associations between male circumcision and women's health outcomes up to April 11, 2016. All biomedical (not psychological or social) outcomes in all study types were included. Searches were not restricted by year of publication, or to sub-Saharan Africa. Publications without primary data and not in English were excluded. We extracted data and assessed evidence on each outcome as high, medium, or low consistency on the basis of agreement between publications; outcomes found in fewer than three publications were indeterminate consistency. Findings: 60 publications were included in our assessment. High-consistency evidence was found for five outcomes, with male circumcision protecting against cervical cancer, cervical dysplasia, herpes simplex virus type 2, chlamydia, and syphilis. Medium-consistency evidence was found for male circumcision protecting against human papillomavirus and low-risk human papillomavirus. Although the evidence shows a protective association with HIV, it was categorised as low consistency, because one trial showed an increased risk to female partners of HIV-infected men resuming sex early after male circumcision. Seven outcomes including HIV had low-consistency evidence and six were indeterminate. Interpretation: Scale-up of male circumcision in sub-Saharan Africa has public health implications for several outcomes in women. Evidence that female partners are at decreased risk of several diseases is highly consistent. Synergies between male circumcision and women's health programmes should be explored. Funding: US Centers for Disease Control and Prevention and Jhpiego.